Hubungan antara Tingkat Pendidikan dengan Pengetahuan Dan Sikap Ibu Tentang Pemberian Imunisasi BCG Pada Bayi Usia 0-2 Bulan di Wilayah Kerja Puskesmas Kebakkramat I Karanganyar - Wijaya, Dedy Tri; Hardjanti, Endang Sri; Hartanto, Rifai (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2013)
Background: Mothers role is very important in BCG immunization to their babies, because immunization is useful to prevent and break the chain of TB disease. This research aims to prove that the degree of education has a strong correlation with the knowledge and attitude of mothers in BCG immunization. Methods: This study was observational analytic conduct by cross-sectional approach. The study was conducted in July-September 20 012 health centers in the working area Kebakkramat I, Karanganyar. Sample of 45 mothers were selected by purposive quota sampling. The variables studied include degree of educational as independent variables, the knowledge and attitudes of mothers about BCG immunization as the dependent variables. This research tool used questionnaires to measure all these variables and have done test validity and reliability. Data were analyzed using kolmogorov-Smirnov models using SPSS 17 for windows. Results: This study shows that the degree of education has a significant association with increased knowledge (kolmogorov-Smirnov Z= 1,375 ; p=0,046) but did not have a significant association with maternal attitudes about BCG immunization (Kolmogorov-Smirnov Z = 1.167, p = 0.131). Conclusion: There is a significant correlation between the degree of education with knowledge of BCG immunization and there is no significant relationship between the level of maternal education and attitudes about BCG immunization. Keywords: Degree of education, Knowledge, Attitute, BCG immunization